The impact of a new container port on the greenhouse gas pollution - David Bogataj; Francisco Campuzano Bolarín; José Andrés Moreno Nicolás (Business Systems Research (BSR), 2024)
Background Large vessels that call at European ports will have to pay for their CO2 emissions from transporting cargo that enters or goes from a European port since January 2024. The costs will increase with increasing global trade. This results in a higher pollution level, including greenhouse gas (GHG) emissions like CO2. Methods/ Approach Based on the gravity model embedded in a global supply chain, we developed a model to evaluate maritime transport pollution in case a new, sufficiently large container port becomes operational. Additionally, we consider how lousy railway connections to European customers increase transportation costs and pollution. Results The approach to the well-connected sequences of gravity models in the intercontinental maritime chains evaluates the differences in quantities of cargo between ports when a new port is opened, and the waiting time does not change. We also highlight that poor rail connections can reduce this positive effect. Conclusions We showed how it is possible to estimate the optimal capacity of a new port with a multi-level gravity model and how this would affect the pollution around the port and on the routes from the port to the final consumers.
Keywords: 330; gravity model; supply chain; seaport; pollution; intercontinental transport; container terminal; railway; CO2 emissions